Is There a Culture War? : A Dialogue on Values and American Public Life - Hunter, James Davison, 1955- (Book collections on Project MUSE., 2006)
Red and Blue states ... the ''Religious Right'' and the ''Liberal Media'' ... NASCAR dads and soccer moms ... Is America clearly and bitterly divided? Are today's social and political differences truly worrisome, or the unavoidable products of a diverse democracy? In Is There a Culture War? two leading authorities on political culture lead a provocative examination of division and unity within America.